Identification and validation of WISP1 as an epigenetic regulator of metastasis in oral squamous cell carcinoma. Issue 1 (22nd September 2015) - Clausen, Martijn J. A. M.; Melchers, Lieuwe J.; Mastik, Mirjam F.; Slagter‐Menkema, Lorian; Groen, Harry J. M.; van der Laan, Bernard F. A. M.; van Criekinge, Wim; de Meyer, Tim; Denil, Simon; Wisman, G. Bea A.; Roodenburg, Jan L. N.; Schuuring, Ed
Abstract : Lymph node (LN) metastasis is the most important prognostic factor in oral squamous cell carcinoma (OSCC) patients. However, in approximately one third of OSCC patients nodal metastases remain undetected, and thus are not adequately treated. Therefore, clinical assessment of LN metastasis needs to be improved. The purpose of this study was to identify DNA methylation biomarkers to predict LN metastases in OSCC. Genome wide methylation assessment was performed on six OSCC with (N+) and six without LN metastases (N0). Differentially methylated sequences were selected based on the likelihood of differential methylation and validated using an independent OSCC cohort as well as OSCC from The Cancer Genome Atlas (TCGA). Expression of WISP1 using immunohistochemistry was analyzed on a large OSCC cohort ( n = 204). MethylCap‐Seq analysis revealed 268 differentially methylated markers. WISP1 was the highest ranking annotated gene that showed hypomethylation in the N+ group. Bisulfite pyrosequencing confirmed significant hypomethylation within the WISP1 promoter region in N+ OSCC ( P = 0.03) and showed an association between WISP1 hypomethylation and high WISP1 expression ( P = 0.01). Both these results were confirmed using 148 OSCC retrieved from the TCGA database. In a large OSCC cohort, high WISP1 expression was associated with LN metastasis ( P = 0.05), disease‐specific survival ( P = 0.022), and regional disease‐free survival ( P = 0.027). These data suggest that WISP1 expression is regulated by methylation and WISP1 hypomethylation contributes to LN metastasis in OSCC. WISP1 is a potential biomarker to predict the presence of LN metastases. © 2015 Wiley Periodicals, Inc.